Sistem Pendukung Keputusan Untuk Pemilihan Auditor dengan Menggunakan Metode MOOSRA - Ahlan Ismono (STMIK Budi Darma, 2022)
Auditors have an important role in the company. This is because the results of the auditor's work are related to the continuity of the company's organization. The role of the auditor is so important for the company that the auditor should have extensive knowledge and good analytical skills. in the selection process does not have a special reference that causes the selected auditor is not in accordance with what is expected by the company. Therefore, it is necessary that the process for selecting auditors has been computerized with a computer. Decision Support System is a system that is already connected to a computer. Decision Support System is part of an information system on a computer that is used to process data. The Multi-objective Optimization method on the basis of Simple Ration Analysis (MOOSRA) is a method that can be used to solve problems on semi-structured and multidisciplinary attributes. The results showed that Alternative 1 (A1) was chosen as the auditor with the highest score of 5.60